A Rare Case of Diffuse-type Tenosynovial Giant Cell Tumor in a Teenager With Noonan Syndrome. Issue 2 (15th March 2022) - Guiffre, Danielle; Brien, Earl; Shon, Wonwoo; Geffner, Mitchell E.
Abstract : Noonan syndrome is a common autosomal dominant disorder associated with an increased risk of malignancy. We report a 16-year-old female with Noonan syndrome ( KRAS gene variant, Q22R) and diffuse-type tenosynovial giant cell tumor, a proliferative disorder that has been rarely reported in this population. These tumors may represent a complication of the dysregulated RAS/MAPK signaling pathway that underlies Noonan syndrome. They lack typical clinical features, causing misdiagnosis and delays in management, which could lead to osseous invasion requiring more complicated surgical procedures. Increased awareness of this association will improve the clinical outcomes of patients with Noonan syndrome who develop diffuse-type tenosynovial giant cell tumors.